Ответ:
1)(x-2)-49=0
(x-2-7)*(x-2+7)=0
(x-9)x(x+5)=0
x-9=0
x+5=0
x=9
x=-5
=-5,=9
2) 9(2x+3)-25=0
(3(2x+3)-5)*(3(2x+3)+5)=0
(6x+9-5)*(6x+9+5)=0
(6x+4)*(6x+14)=0
2(3x+2)*2(3x+7)=0
(3x+2)*(3x+7)=0
3x+2=03x+7=0
x=-2/3
x=-7/3
=-7/3,=-2/3
3) 2(3x+5)=7(3x+5)
2(9+30x+25)=21x+35
18+60x+50=21x+35
18+60x+50-21x-35=0
18+39x+15=0
6+13x+5=0
6+10x+3x+5=0
2*(3x+5)+3x+5=0
3(x+5)*(2x+1)=0
3x+5=0
2x+1=0
x=-5/3
x=-1/2
=-5/3,=-1/2
4) (3x-1)=4-12x
9-6x+1=4-12x
9-6x+1-4+12x=0
9+6x-3=0
3+2x-1=0
3+3x-x-1=0
3x*(x+1)*(3x-1=0
x+1=0
3x-1=0
x=-1
x=1/3
=-1,=1/3
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
1)(x-2)
-49=0
(x-2-7)*(x-2+7)=0
(x-9)x(x+5)=0
x-9=0
x+5=0
x=9
x=-5
2) 9(2x+3)
-25=0
(3(2x+3)-5)*(3(2x+3)+5)=0
(6x+9-5)*(6x+9+5)=0
(6x+4)*(6x+14)=0
2(3x+2)*2(3x+7)=0
(3x+2)*(3x+7)=0
3x+2=03x+7=0
x=-2/3
x=-7/3
3) 2(3x+5)
=7(3x+5)
2(9
+30x+25)=21x+35
18
+60x+50=21x+35
18
+60x+50-21x-35=0
18
+39x+15=0
6
+13x+5=0
6
+10x+3x+5=0
2
*(3x+5)+3x+5=0
3(x+5)*(2x+1)=0
3x+5=0
2x+1=0
x=-5/3
x=-1/2
4) (3x-1)
=4-12x
9
-6x+1=4-12x
9
-6x+1-4+12x=0
9
+6x-3=0
3
+2x-1=0
3
+3x-x-1=0
3x*(x+1)*(3x-1=0
x+1=0
3x-1=0
x=-1
x=1/3